Tendensi Politik Kejahatan Dunia Maya - Launa; Bambang Mudjiyanto; Franky P. Roring (Universitas Majalengka, 2024)
ABSTRACT This study aims to search a number of data, documents and literature to explore cyber crimes which are not only economically motivated, but also have political tendencies. Various cases of data hacking carried out by regional and global hackers and crackers have positioned cyber space as an arena for aggressive political contestation that has shaken the foundations of political, military, defense, security and intelligence life. The concept of cybersecurity is currently projected to protect national interests/sovereignty (cyberdefence) through developing cyberwar and cyberdiplomacy strategies to overcome the increasingly intense threat of cybercrime. This qualitative study using a descriptive analysis method based on a literature study approach tries to analyze the political tendencies underlying the motives for cybercrime, both at the global and national levels. The results of the study show: cyber space in many countries (including Indonesia) has been transformed into an arena of aggression and a realm of political contestation which—if not anticipated through breakthroughs and extra efforts—has the potential to thwart Indonesia in safeguarding its national interests, maintaining the sovereignty of its citizens from cyber threats, and it is difficult to expose Indonesia's national diplomatic capabilities in responding to cyber crimes that continue to move wildly. Keywords: Cybercrime, political tendencies, cyber diplomacy, cyber security, cyber defense, cyber war ABSTRAK Studi ini bertujuan melakukan penelusuran sejumlah data, dokumen, dan literatur untuk mengeksplor kejahatan dunia maya yang tak hanya bermotif ekonomis, namun juga bertendensi politis. Beragam kasus peretasan data yang dilakukan para hacker dan cracker regional dan global telah memosisikan ruang siber sebagai arena agresi kontestasi politik yang telah menggoncang sendi-sendi kehidupan politik, militer, pertahanan, keamanan, dan intelijen. Konsep cybersecurity saat ini lebih diproyeksikan untuk menjaga kepentingan/kedaulatan nasional (cyberdefence) melalui penyusunan strategi cyberwar dan cyberdiplomacy guna mengatasi ancaman kejahatan siber yang kian intens. Studi kualitatif dengan metode analisis deskriptif berbasis pendekatan studi pustaka ini coba menganalisis tendensi politik yang melatari motif kejahatan dunia maya, baik di level global maupun di nasional. Hasil studi menunjukkan: ruang siber di banyak negara (termasuk Indonesia) telah bertransformasi menjadi arena agresi dan ranah kontestasi politik yang—jika tidak diantisipasi dengan terobosan dan upaya ekstra—berpotensi menggagalkan Indonesia dalam menjaga kepentingan nasionalnya, merawat kedaulatan warganya dari ancaman dunia siber (cyber defence), dan sulit mengekspose kapasitas diplomasi nasional Indonesia dalam merespon tindak kejahatan dunia maya yang terus bergerak liar. Kata-kata Kunci: Kejahatan dunia maya, tendensi politik, diplomasi siber, keamanan siber, pertahanan siber, perang siber